2000
DOI: 10.1161/01.hyp.35.3.726
|View full text |Cite
|
Sign up to set email alerts
|

ET B Receptor Blockade Potentiates the Pressor Response to Big Endothelin-1 But Not Big Endothelin-2 in the Anesthetized Rabbit

Abstract: Abstract-The precursor of endothelin-1, big endothelin-1, is considered to be a more reliable marker of systemic production of vasoactive peptide. However, it is largely unclear whether ET B receptor-dependent clearance and endothelium-derived relaxing factors affect the precursor in a similar manner to mature ET-1. These ET B -dependent modulations of big ET-1 and big ET-2 pressor properties were therefore studied in the anesthetized rabbit. When injected into the left cardiac ventricle, ET-1 and ET-2 (0.01 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…In contrast, the ET B antagonist BQ-788 (0.25 mg/kg) potentiated the increases in MAP afforded by big ET-1 (as reported previously) 15 and ET-1 (1-31) (Figure 3).…”
Section: Contribution Of Et Receptors To Pressor Responses To Et-1 (1supporting
confidence: 85%
See 4 more Smart Citations
“…In contrast, the ET B antagonist BQ-788 (0.25 mg/kg) potentiated the increases in MAP afforded by big ET-1 (as reported previously) 15 and ET-1 (1-31) (Figure 3).…”
Section: Contribution Of Et Receptors To Pressor Responses To Et-1 (1supporting
confidence: 85%
“…We had shown previously in this same animal model that big ET-1 was converted in the circulation to ET-1 via a phosphoramidon-sensitive process, 15 suggesting that the precursor was inactive per se. Nakano et al 2 reported the existence of ET-1 (1-31), and Hayasaki-Kajiwara et al 4 suggested that this particular intermediate could generate ET-1 via an ECE/NEP process in human cultured bronchial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations